Effectiveness of Drying Methods on The Quality and Physicochemical Characteristics of Dried Gac Fruit (Momordica cochinchinensis Spreng) - Bunga Raya Ketaren; Desi Ardilla; M. Thamrin; Aisar Novita; Hilda Julia; Efrida Lubis (JURNAL AGRONOMI TANAMAN TROPIKA (JUATIKA), 2025)
Gac fruit is renowned for its rich content of bioactive compounds, including lycopene, β-carotene, and vitamin E, which provide significant health benefits. However, due to its high moisture content, the fruit is highly perishable and requires proper postharvest handling to extend its shelf life. Drying is one of the most common preservation techniques employed to retain nutritional and functional qualities while reducing water activity. This study aims to evaluate the influence of different drying methods, specifically oven drying, vacuum drying, and sunlight drying. The results indicate that vacuum drying exhibits the highest IC50 inhibition compared to both solar and oven drying methods; however, there is no significant difference in inhibition between the solar and oven drying methods. In lightness (L value), sunlight and vacuum drying result in darker colors than oven drying. Still, there is no significant difference in brightness between sunlight and oven drying. The solar drying method exhibited the highest weight loss at 87.45%. However, there was no significant difference in the drying efficiency between the oven and vacuum oven methods. Microbial contamination under sunlight appears to be higher than in oven and vacuum drying; nonetheless, all methods remain acceptable as they fall below the safe limit. Based on these results, oven drying was selected for Gac fruit drying due to its favorable physicochemical outcomes and the shortest drying time. Additionally, oven drying proved to be the most balanced method, providing good retention of bioactive compounds, effective moisture removal, and acceptable microbial stability. Furthermore, oven drying produced the most visually appealing red hue, likely attributed to enhanced lycopene stability.